Imaging characteristics of intravascular spherical contrast agents for grating-based x-ray dark-field imaging – effects of concentrations, spherical sizes and applied voltage - Notohamiprodjo, Susan; Treitl, Karla Maria; Hauke, Christian; Sutter, Sven Martin; Auweter, Sigrid; Pfeiffer, Franz; Reiser, Maximilian Ferdinand; Hellbach, Katharina (Scientific Reports, 2020)
This study investigates the x-ray scattering characteristics of microsphere particles in x-ray-grating-based interferometric imaging at different concentrations, bubble sizes and tube voltages (kV). Attenuation (ATI), dark-field (DFI) and phase-contrast (PCI) images were acquired. Signal-to-noise (SNR) and contrast-to-noise ratios with water (CNRw) and air as reference (CNRa) were determined. In all modalities, a linear relationship between SNR and microbubbles concentration, respectively, microsphere size was found. A significant gain of SNR was found when varying kV. SNR was significantly higher in DFI and PCI than ATI. The highest gain of SNR was shown at 60 kV for all media in ATI and DFI, at 80 kV for PCI. SNR for all media was significantly higher compared to air and was slightly lower compared to water. A linear relationship was found between CNRa, CNRw, concentration and size. With increasing concentration and decreasing size, CNRa and CNRw increased in DFI, but decreased in PCI. Best CNRa and CNRw was found at specific combination of kV and concentration/size. Highest average CNRa and CNRw was found for microspheres in ATI and PCI, for microbubbles in DFI. Microspheres are a promising contrast-media for grating-based-interferometry, if kV, microsphere size and concentration are appropriately combined.
CRIS-Team Scopus Importer:2020-06-19